In vivo alteration of humoral responses to HIV-1 envelope glycoprotein gp120 by antibodies to the CD4-binding site of gp120 - Visciano, Maria Luisa (2007)
The binding of antibodies to the CD4-binding site (CD4bs) of the HIV-1 envelope glycoprotein gp120 has been shown to induce gp120 to undergo conformational changes that can expose and/or shield specific epitopes on gp120. Here, we study alterations in the antigenicity and immunogenicity of gp120 when complexed with human monoclonal antibodies (mAbs) specific for the CD4bs of gp120. The data showed that gp120 bound by anti-CD4bs mAbs had enhanced reactivity with mAbs to the V3 and N-terminal regions, but not with mAb to the C terminus. Moreover, mice immunized with the gp120/anti-CD4bs mAb complexes produced higher titers of gp120-specific serum IgG and IgA than mice immunized with uncomplexed gp120 or other gp120/mAb complexes. Notably, the enhanced antibody production was directed against V3 and correlated with better exposure of V3 on the gp120/anti-CD4bs mAb complexes. The higher antibody reactivity was evident against the homologous V3(LAI) peptide, but not against heterologous V3 peptides. Potent neutralization activity against HIV-1(LAI) was also observed in the sera from mice immunized with gp120/anti-CD4bs mAb complexes, although the sera exhibited poor neutralizing activities against other viruses tested. These results indicate that the anti-CD4bs antibodies alter the antigenicity and immunogenicity of gp120, leading to enhanced production of anti-gp120 antibodies directed particularly against the V3 region.